The phytochemistry, pharmacology and traditional medicinal use of Glechomae Herba – a systematic review. Issue 31 (27th May 2021) - Yang, Liu; Zhang, Jiaxu; Zheng, Senwang; Hou, Ajiao; Wang, Song; Yu, Huan; Wang, Xuejiao; Xu, Yingjie; Kuang, Haixue; Jiang, Hai
Abstract : Glechomae Herba is a Chinese herb, which has been used in China for thousands of years, mainly for the treatment of nephrolithiasis. Abstract : Glechomae Herba is a Chinese herb, which has been used in China for thousands of years, mainly for the treatment of nephrolithiasis. This paper summarizes the modern research progress on Glechomae Herba from the aspects of botany, traditional medicinal use, phytochemistry, pharmacology, pharmacokinetics, analytical methods and quality control. In addition, it also points out the deficiencies of current research on this herb and provides possible directions for its development. So far, more than 190 chemical components have been isolated and identified from Glechomae Herba, including organic acids and their esters, volatile oils, flavonoids and their glycosides, terpenes and other chemical components. Its extracts and compounds have a wide range of pharmacological effects, including anti-stone, anti-inflammatory, bacteriostatic, cholagogic and diuretic, effect on ileum smooth muscle, anti-tumor effect on tumor and hypoglycemic effects. However, future studies should focus on drug metabolism, clarify its pharmacodynamic mechanism, and establish a reasonable quality control standards for Glechomae Herba .